Rethinking connectedness: improving access to professional learning for regional and remote teachers - Broadley, Tania (Australian Association for Research in Education, 2011)
Transformation of Australian education is occurring at a rapid rate through the implementation of a number of initiatives. These initiatives include the Digital Education Revolution, the move to a National Curriculum and the implementation of a National Framework for Professional Standards for Teachers and Principals. As these initiatives are rolled out to schools across Australia, the equitable access to professional learning to support all teachers, regardless of their geographical location, is in question. A number of studies have been conducted in Australia that highlight the importance of professional learning and the difficulty faced by regional and remote teachers with regard to access (Gerard Daniels, 2007; Lysons, Cooksey, Panizzon, Parnell & Pegg 2006; Ministerial Review of Schooling, 1994, Rural and Remote Education Advisory Council, 2000; Vinson, 2002). Along with access to professional learning, has been the discussion of effective modes of delivery. Face to face professional learning, in regional and metropolitan areas, is offered in isolation, or in some cases, is complimented with virtual learning environments. The need for a more sustainable approach to professional learning is highly necessary. A mixed method research approach was utilised in order to answer the primary research question "In what ways might technology be used to support professional learning of regional and remote teachers in Western Australia?"This research paper outlines the findings from the study including the significance of travel time; impact of limited relief teachers; implications for promotion and teacher registration; professional learning communities being valued but often limited by small staff numbers; professional learning conducted in the local context being preferred; professional learning established at the teacher and school level being desirable; teachers being confident in using technology and accessing PD online if required; and social cohesiveness being valued and often limited by isolation. Further, this research has culminated in the development of a "model of rethinking connectedness" that would facilitate improving the amount and variety of professional learning available to regional and remote teachers.